Role of Extracellular Vesicles in Influenza Virus Infection - Jiang, Yuan; Cai, Xiaowen; Yao, Jiwen; Guo, Huanhuan; Yin, Liangjun; Leung, Wingnang; Xu, Chuanshan (Frontiers in Cellular and Infection Microbiology, 2020)
Influenza virus infection is a major health care concern associated with significant morbidity and mortality worldwide, and cause annual seasonal epidemics and pandemics at irregular intervals. Recent research has highlighted that viral components can be found on the extracellular vesicles (EVs) released from infected cells, implying a functional relevance of EVs with influenza virus dissemination. Therefore, exploring the role of EVs in influenza virus infection has been attracting significant attention. In this review, we will briefly introduce the biogenesis of EVs, and focus on the role of EVs in influenza virus infection, and then discuss the EVs-based influenza vaccines and the limitations of EVs studies, to further enrich and boost the development of preventative and therapeutic strategies to combat influenza virus.